The Study of Relation Among Green Bonds and Other Financial Assets: A Systematic Literature Review - Nurvita, Tita; Achsani, Noer Azam; Anggraeni, Lukytawati; Novianti, Tanti (Indonesian Journal of Sustainability Accounting and Management, 2023)
The purpose of this study is to provide a literature review of green bonds and their relation with other financial assets. Most of the research that has been conducted has focused on the spillover transmission from the financial asset market to the green bond market. The method used to select and analyze the results of journal reviews is Preferred Reporting Items for Systematic Reviews and Meta- Analyses (PRISMA). The journals used in this study are Scopus-indexed journals, which are searched using the keywords green bond, cointegration, transmission, and spillover. The result indicates that green bonds can be used as an alternative in diversifying portfolio instruments. Based on previous studies, it was found that there was spillover transmission from the financial asset market to the green bond market. This indicates that volatility in the financial market will spill over and affect the green bond market. This study can be used as a strategy for making investment decisions, especially in building investment portfolios.